PENGARUH KOMBINASI PUPUK KANDANG DAN NPK TERHADAP PRODUKSI SEGAR DAN RATIO DAUN BATANG RUMOT GAJAH MINI (Pennisetum purpureum cv. Mott) DEFOLIASI KE TIGA - Dharmaseno Valgunadi; Bahrun Bahrun; Nur Hidayat (ANGON: Journal of Animal Science and Technology, 2020)
Background. The study entitled "Effect of Combination of Manure and NPK Fertilizer on Fresh Production and Ratio Leaf Stem of Dwarf Elephant Grass (Pennisetum purpureum cv. Mott) third Defoluation was conducted from November 19th to December31st 2018 at Experimental Farm and Agrostology Laboratory, Faculty of Animal Husbandry, Jenderal Soedirman University, Purwokerto . The purpose of these study was to examine the effect of applying manure and NPK fertilizer with the use of optimal fertilizer doses on fresh production and leaf stem ratio dwarf elephant grass. Materials and Methods. The materials used in this study were 720 of pols, 270 kg of manure, 2.5 kg of NPK fertilizer. The method used is factorial pattern experiments with random complete block designs. The first factor is manure consisting of K0: 0 kg / 5m2, K1: 7.5 kg / 5m2, K2: 15 kg / 5m2 and the second factor is NPK (M) consisting of M0: NPK 0 g / 5m2, M1: NPK 37.5 g / 5m2, M2: NPK 75 g / 5m2 and M3: NPK 112.5 g / 5m2. The measured variable is the Fresh Production and the Ratio of Leaves and Stems from the third Defolation. Results. The average value of fresh production results obtained in each treatment up and down K0M0 = 6.71 ± 0.112. K0M1 = 6.87 ± 0.104, K0M2 = 6.82 ± 0.042, K0M3 = 8.55 ± 0.192, K1M0 = 7.33 ± 0.440, K1M1 = 7.69 ± 0.421, K1M2 = 7.91 ± 0.170, K1M3 = 7.33 9.94 ± 1.30, K2M0 = 9.35 ± 0.280, K2M1 = 8.20 ± 0.410, K2M2 = 10.46 ± 0.142, K2M3 = 11.21 ± 0.205kg/unit. The average value of the ratio of stem leaves. K0M0 = 3.65 ± 0.12. K0M1 = 3.85 ± 0.293, K0M2 = 4.22 ± 0.083, K0M3 = 4.60 ± 0.049, K1M0 = 3.63 ± 0.255, K1M1 = 4.75 ± 0.202, K1M2 = 5.27 ± 0.194, K1M3 = 0.63 5.43 ± 0.140, K2M0 = 5.67 ± 0.075, K2M1 = 5.64 ± 0.110, K2M2 = 5.54 ± 0.081, K2M3 = 7.11 ± 0.278 Results of the analysis of variance showed that the application of manure was highly significant (P<0.01) and NPK fertilizer application were also significant (P <0.05) in Fresh Production. The application of manure to the leaf stem ratio was also significant (P <0.05) and the application of NPK fertilizer was highly significant (p <0.01). Conclusion. The higher dose of manure and NPK will increase the fresh production and ratio of stem leaves.